TREND OF REALIZED GENETIC GAIN OBSERVED IN SECOND-GENERATION SEEDLING SEED ORCHARDS OF ACACIA MANGIUM IN SOUTH KALIMANTAN, INDONESIA - Arif Nirsatmanto; Teguh Setyaji; Surip Surip (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2013)
Comprehensive tree improvement program for Acacia mangium has been started since 1992 by establishing a series of first generation Seedling Seed Orchards (SSO) in Indonesia. Selection procedures in the first-generation of SSO have completely finished, and subsequently it was continued for second-generation improvement. This paper examines a trend of realized genetic gain as a response of selection practiced in the first-generation SSO. The observation was carried out in three sub-lines of the second-generation SSO (namely Sub-line B, C and D). Parameters recorded included tree height, diameter at breast height (dbh) and stem straightness that were recorded periodically up to 4 years growth. The realized genetic gain was calculated as a percentage of improved plus trees population in the first-generation of SSO compared to those of unimproved trees. The results showed that the improved population was consistently better that those of unimproved one until 4 years of age. There were variation in terms of realized genetic gain parameters recorded depending on the sub-lines and ages. The tree height varied from 1.1% to 5%, while dbh and stem straightness were in the ranges of 2.8% to 6.7% and from 1.8% to 8.4%, respectively. Across the three sub-lines, the tree height varied from 2.2% to 3.1%, while dbh and stem straightness were in the ranges of 4.3% to 5.2% and 4.3% to 6%, respectively. In general, the trend of the realized genetic gains slightly decreased for dbh and tree height with the increasing of ages, while it slightly increased for stem straightness.